Lung ultrasound–guided positioning strategy for the prevention of ventilator-associated pneumonia in neonates - Liang, Zhenyu; Li, Binghui; Zhang, Xiao; Li, Lin; Xu, Debo; Meng, Qiong; Huang, Xihua; Li, Huiyi (Frontiers in Pediatrics, 2026)
ObjectiveTo determine whether a lung ultrasound–guided positioning strategy reduces the incidence of ventilator-associated pneumonia (VAP) in mechanically ventilated neonates compared with conventional empiric repositioning.Data sourcesA prospective, randomized controlled trial.InterventionsIn this prospective, randomized controlled trial, term neonates requiring invasive mechanical ventilation for more than 48 h were enrolled in the Level III NICU of Guangdong Second Provincial General Hospital from December 2023 to December 2025. Eligible infants were randomly assigned (1:1) to receive either conventional positioning or LUS-guided positioning management. The LUS-guided group underwent twice-daily bedside ultrasound assessments to detect atelectasis or consolidation, and posture was adjusted accordingly to optimize dependent drainage and ventilation–perfusion matching. The primary outcome was the incidence of VAP. Secondary outcomes included duration of mechanical ventilation, feeding intolerance, pulmonary hemorrhage, pneumothorax, new-onset intracranial hemorrhage, mortality, and NICU length of stay.ResultsA total of 94 neonates were randomized (47 per group), and 89 completed follow-up. Baseline characteristics were comparable between groups. The incidence of VAP was significantly lower in the LUS-guided group than in the control group (17.8% vs. 38.6%, p = 0.017), with an unadjusted odds ratio (OR) of 0.28 (95% CI, 0.13–0.90) and an adjusted OR of 0.32 (95% CI, 0.12–0.86, p = 0.024). The LUS-guided group also showed a shorter duration of mechanical ventilation [median (IQR): 11.0 (9.0–13.0) vs. 12.0 (10.0–14.0) days, p = 0.023], with a mean difference of −1.4 days (95% CI, −2.6 to −0.2). No significant differences were observed in other secondary outcomes, including pulmonary hemorrhage, pneumothorax, feeding intolerance, new intracranial hemorrhage, or mortality (all p > 0.05).ConclusionLung ultrasound–guided positioning significantly reduced the incidence of ventilator-associated pneumonia and shortened ventilation duration without increasing adverse events. This physiologically informed, radiation-free approach enables individualized postural management to optimize lung aeration and secretion clearance. LUS-guided care is feasible, safe, and easily integrated into NICU workflows, providing a promising adjunct to standard VAP prevention bundles. Further multicenter, adequately powered trials and cost-effectiveness studies are warranted to confirm these findings and support broader clinical adoption.